Progeria : Pathogenesis and Oral Manifestation- A Review - Saigal, S; Bhargava, A (Kathmandu University Medical Journal, 2012)
Our life span is genetically programmed and it is possible that a defect in produced proteins encoded by the ‘longevity’ gene is a cause of aging. Progeria which is a rare, fatal genetic condition which affects between one in four million and one in eight million children of both sexes equally and characterized by premature and accelerated aging. The appearance and physiology of these children resembles to elderly people but they typically have life span to their mid teens. It is also known as the Hutchinson-Gilford syndrome, which was initially reported by Johnathan Hutchinson in 1886 and further described by Hastings Gilford in 1904. It is an autosomal recessive disorder, which means an individual has inherited a mutated gene from both parents. It is added to the expanding catalogue of ‘laminopathies’, diseases caused by mutations affecting nuclear lamina proteins known as lamin A (LMNA). In oral manifestation primary finding is micrognathia with delayed tooth eruption and incomplete formation of root of permanent tooth. Presently there are no known cures for this abnormality. KATHMANDU UNIVERSITY MEDICAL JOURNAL  VOL.10 | NO. 1 | ISSUE 37 | JAN - MAR 2012 | 72-76 DOI: http://dx.doi.org/10.3126/kumj.v10i1.6919